IMPLEMENTASI KEBIJAKAN PELAYANAN ADMINISTRASI KEPENDUDUKAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA BITUNG - SIWU, ANGIE (Sam Ratulangi University, 2013)
ABSTRACT : population policy administration services stipulated in Law no. 23 of 2006 , and further elaborated in the PP . No. . 37 of 2007 and Presidential Regulation . 25 of 2008 . As a follow up of the policy then issued Regulation No. Bitung City . 5 of 2007 on the organization of registration Population and Civil Registration in Bitung , and Regulation 6 of 2007 on Population Registration Fees and Civil Registration in Bitung City , Bitung Mayor Regulation Number Number 24 Year 2008 on Details of Duties, Functions and Administration of the Department of Population and Notes civil Bitung City . This study is to answer the question of how the implementation of population policies in the service of the Department of Civil Kependudukandan Bitung City . The method used in this study is a qualitative method . The focus of the research is the implementation of